Teacher Retention in Private Schools of Nepal: A Case from Bhaktapur District - Shrestha, Rajan Kumar (KMC Journal, 2022)
Retention of qualified teachers is a crucial part for the quality education in schools because qualified, experienced and stable teachers can enhance the academic standard of students. It is equally important for the smooth operation and success of schools. Considering these facts, a quantitative research with correlational research design was carried out with the objective of finding out relationship between teacher retention and domains of its determinants in private schools of Bhaktapur district, Nepal. The data was collected through a questionnaire. This study concluded that financial and school culture domains have a powerful and significant impact on teacher retention. Similarly, there is a significant association between teacher retention and social domain, and between teacher retention and emotional domain. This study suggested that school administrators and policy makers need to understand that there is a strong positive impact of financial domain and school culture domain on teacher retention. They need to formulate policies which can satisfy financial needs and create a good school culture. Similarly, they need to improve teacher retention by addressing emotional domain and social domain.